FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN FASILITAS E-FILLING DALAM PENYAMPAIAN SPT MASA OLEH WAJIB PAJAK DI KOTA BENGKULU - Hesti Setiorini; Yusmaniarti Yusmaniarti (Universitas Muhammadiyah Bengkulu, 2020)
The title of this study is the factors that influence the use of e-filling tax facilities by taxpayers as a means of submitting effectively and efficiently annual notice (SPT) in Pratama tax service office of Bengkulu city. In the use of e-filling facilities, not all taxpayers use it for various reasons. This study aims to find out the empirical evidence of the influence of perception of usefulness (X1), perception of easiness (X2), complexity (X3), security and confidentiality (X4), taxpayer information technology readiness (X5), and counseling to taxpayers (X6) toward the intensity of behavior in the use of e-filling (y) in the Pratama tax service office of Bengkulu city. In this study, the samples taken were 100 taxpayers registered in the Pratama tax service office of Bengkulu City. Data collection is done through direct observation and surveys, and the data were obtained by distributing questionnaires to the respondents. This study uses Technology Acceptance Models (TAM) with the SPSS program. The results showed that the perception of usefulness (X1) had a significant positive influence on the intensity of behavior for the use of e-filling. Easiness perception (X2) had a positive significant influence on the intensity of behavior for the use of e-filling, Complexity (X3) had significant negative influence on the intensity of behavior for e-filling, security and confidentiality (X4) had significant positive influence on the intensity of behavior for filling the e-filling, taxpayer information technology readiness (X5) had a significant positive influence on the intensity of behavior for filling the e-filling, and counseling to taxpayers (X6) had a significant positive influence on the intensity of behavior for filling the e-filling.Â Keywords: Perception of Usability, Perception of Convenience, Complexity, Security and Confidentiality, Taxpayer Information Technology Readiness and counseling to Taxpayers on Behavioral Intensity in the Use of E-Filling.